Bentuk Penyajian Gandang Sarunai Pada Upacara Adat Turun Bako Di Koto Panjang Surantih Pesisir Selatan - Mutia Padila; Marzam Marzam (FBS Universitas Negeri Padang, 2021)
This study aims to reveal and describe the form of presentation of Gandang Sarunai in the Turun Bako Traditional Ceremony in Koto Panjang Surantih District, Pesisir Selatan Regency. This type of research in the form of presentation of Gandang Sarunai is qualitative with descriptive method. The research instrument in this study was the researcher himself and was assisted by supporting instruments such as writing instruments and cameras. Data collection techniques were carried out by means of observation, literature study and interviews. The steps to analyze the data are collecting data, describing the data, and concluding the data. The results showed that the form of presentation of Gandang Sarunai Koto Panjang Pesisir Selatan Regency at the time of staging the Turun Bako traditional ceremony was not much different from other regions, starting from the opening, content and closing. At the opening, Gandang Sarunai played the song to inform the community that he would be parading the children of anak daro or marapulai back home. The content in the Gandang Sarunai performance is the cast of Gandang Sarunai parading the anak daro or marapulai home, with the child of the daro or marapulai in the first row, the second row of Bako and the last row of the Gandang Sarunai players. The closing part of the Gandang Sarunai performance is the arrival of anak daro or marapulai who are paraded to their homes, here the Gandang Sarunai players continue to play the instrument, to entertain the delivery at the baralek location.